GAMBARAN KADAR CARBOHYDRATE ANTIGEN 19-9 ( CA 19-9 ) PADA PASIEN YANG DI CURIGAI KANKER PANKREAS DI RSUD ABDUL WAHAB SJAHRANIE SAMARINDA PADA TAHUN 2020-2022 - Pondi, Restiyani (Akademi Kesehatan John Paul II Pekanbaru, 2024)
Pancreatic cancer is one of the most fatal cancers and the leading cause of cancer-related deaths. The survival rate for pancreatic cancer in the United States is reported to be 8%, which is another common type of cancer and in Indonesia itself pancreatic cancer is ranked 17th. Ca 19-9 is a cell produced by pancreatic exocrine gland cancer cells and can be detected in blood tests. The purpose of this study was to determine the Description of Ca 19-9 Levels in Pancreatic Cancer Patients at Abdul Wahab Sjahranie Hospital, Samarinda in 2020-2022. The research design used was the type of Analytical Observational method using Cross Sectional, meaning that the variables studied were only imposed once on a number of subjects who were the research samples. The results of the study were collected from medical records in the clinical pathology laboratory at Abdul Wahab Sjahranie Hospital, Samarinda in 2020-2022. From this study, it was found that there were 72 patients suspected of pancreatic cancer, where the majority were <55 years old, and 57% were male. Furthermore, based on the examination of Ca19-9 levels, it was found that 28 patients experienced levels above normal as much as 39%. The conclusion is that patients suspected of pancreatic cancer who underwent Ca 19-9 examination for the first time obtained results above normal levels, there were 28 patients with a percentage of 39% with an average age of > 65 years.